Ni Impregnated Zn/CaO as Heterogeneous Catalyst For Triglyceride Transesterification and Kinetic Modelling - Kumar, Sachin (My University, 2016)
In present work a series of Ni impregnated Zn/CaO has been prepared by varying the Ni concentration in the range of 2-10 wt% by wet impregnation method. The prepared 7-Ni- Zn/CaO catalyst was characterized by Hammett Indicator, powder XRD, FE-SEM and HRTEM and TGA studies. This catalyst was employed for the transesterification of triglycerides to yield fatty acid alkyl esters (FAAE) and then for kinetic modelling by LHHW model. 1HNMR and 13C-NMR techniques were employed to quantify the FAME yield obtained during the transesterification reaction. Under the optimized reaction conditions of 5 wt% catalyst (with respect to oil), 65 ºC reaction temperature, methanol to oil molar ratio 9:1, ≥98% FAME yield was obtained in 1.5 h of reaction duration.
M Sc Dissetation
Keywords: Heterogeneous catalyst; transesterification